ENHANCING STUDENT MOTIVATION AND ACADEMIC PERFORMANCE: AN EXPLORATION OF SELF-DETERMINATION THEORY IN EDUCATIONAL PSYCHOLOGY - Ikromova , G.A; Nurbayeva , Kh.B (Educational Research in Universal Sciences, 2023)
This scientific article delves into the realm of educational psychology, focusing on the application of Self-Determination Theory (SDT) to enhance student motivation and academic performance. The study investigates the impact of autonomy, competence, and relatedness on students’ intrinsic motivation and explores practical strategies for educators to foster a supportive learning environment. Research findings indicate a positive correlation between SDT principles and academic outcomes, emphasizing the significance of autonomy-supportive teaching practices.